A educação musical como agente facilitador do processo de aprendizagem - Araujo, Maria Clara Correa Dantas de (1981)
This dissertation is based on the supposition that music develops the emotional balance of the individual and his sensitivity to beauty. This premise emphasizes the importance of this study, specially relating to other teaching areas, considering the teaching of music as an auxiliary instrument in the learning of other subjects. This is a theoretical study involving pedagogy and having as an objective the importance of music education, not to discover musical talents, but to develop the individual potential to understand and -appreciate music, creating ideal conditions for learning. Several fundamental points are dealt with, showing that music education in school is a basic factor contributing to the emotional balance of the student, helping him in his other areas of study and facilitating his learning process.